Primary temporal bone squamous cell carcinoma with intracranial extension - Sen, Cenk Ahmet; Kaya, Vildan; Miman, Murat Cem; Arslan, Cagatay (European Journal of Oncology and Environmental Health, 2015)
Dear Editor,Primary temporal bone tumors constitute less than 0.2% of all head and neck tumors. Over 85% of these tumors are squamous cell carcinomas (1). The first known case was reported in 1775 and partial surgical resection of the temporal bone was first made in 1954 (2). Primary treatment is surgical resection. Due to the heterogeneity of the tumor location no standard treatment algorithm can be formed. There are few case series or reports in the literature. Here we present a case of temporal bone squamous cell carcinoma.[...]